JOULE HEATING EFFECT ON MHD FREE CONVECTIVE HEAT ABSORBING/GENERATING VISCOUS DISSIPATIVE NEWTONIAN FLUID WITH VARIABLE TEMPERATURE - Raju, A B Madhu Mohana; G, Srinivasa (International Journal of Research -GRANTHAALAYAH, 2017)
In the present theoretical study we have examined Joule heating effect of MHD free convective heat absorbing/generating viscous dissipative Newtonian fluid with the consideration of variable temperature. The governing equations related to the problem are solved for velocity, temperature and concentration by using numerical finite difference scheme. The variations in velocity, temperature and concentration under the effects of several physical parameters are studied and represented with the use of graphs. Also we have recorded the numerical values for local skin friction, rate of heat transfer and rate of mass transfer and discussed their characteristics.